PESAN MORAL DALAM NOVEL SEHIDUP SESURGA KARYA ASMA NADIA - Wahyuniati; Ana Yuliati (Jurnal Sastra Aksara, 2021)
This research is about the moral message in the novel Sehidup Sesurga by Asma Nadia. This study has a purpose, namely to describe the types and forms of moral messages and forms of delivery (1) Types and forms of moral messages in Asma Nadia's novel Sehidup Sesurga, (2) The form of delivery of moral messages in Asma Nadia's Sehidup Sesurga novel. qualitative. The data in this study are in the form of sentences that show the moral message in the novel Sehidup Sesurga by Asma Nadia. This study uses an analysis of the types and forms of moral messages and forms of delivery. Based on research, based on research, the types and forms of moral messages as well as the form of delivery in the novel Sehidup Sesurga by Asma Nadia, there are 116 date. which includes the type of human relationship with God there are 20 date, the type of human relationship with himslef 20 date, the type of human relationship with society 36 data and the form of direct delivery there are 20 date and the form of indirect delivery there are 20 date.